UTILIZATION OF HYDROPONIC VEGETABLE CULTIVATION IN ORDER TO INCREASE COMMUNITY INCOME IN THE SOUTH KEMBANGAN REGION - Orlin, Orlin (Bina Nusantara University, 2024)
Hydroponics is an alternative business opportunity that people can use if they want to increase their income to meet their daily needs. Because, public awareness of healthy food that can be obtained from vegetables grown with good media (without using pesticides) is the basis for the presence of hydroponics which is very popular today. This community service activity that has been carried out socializes the steps in carrying out correct & appropriate hydroponic planting so that the harvested product can be a product with good quality and have a high selling price when on the market. This community service activity which was held on March 16, 2023 in the South Kembangan sub-district hall socialized the use of hydroponic vegetable cultivation to increase community income in the South Kembangan area. Participants who attended this activity were South Kembangan PKK women who directly wanted to learn more about how to plant hydroponic vegetables hydroponically correctly. The aim of the socialization is to help participants in planting hydroponic vegetables in the right way and can be done independently in their respective homes. The results of this community activity resulted in a new understanding for the participants and team from the community activity that hydroponic vegetable planting has techniques that need to be considered in detail by the grower so that the vegetables to be harvested can develop well and have a nice & large shape.